(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Domestic crime, also called domestic violence, is an act of violent abuse directed at a partner, family, or other relationship status. Usually, women are the victims of domestic crime because they are physically weaker than men and are the ones who are subjected to such treatment or action. The common reasons for a person committing domestic crime or violence are that they are angry, that they cannot control themselves from hurting the person they have hurt, or that they are drunk and unaware of what they have done. Nowadays, domestic crime or violence is rampant in many areas. The number of cases of domestic violence is increasing, particularly as the COVID-19 pandemic spreads throughout the Philippines. The researchers want to study the causes of domestic crime or violence, the effects it has on victims, and the various methods of preventing it, as well as how effective they are in implementing it in Barangay San Agustin, Quezon City. The qualitative descriptive will be used in the study. According to the findings of the study, the profile of the respondents is in terms of age; the majority of them are aged 18 and below, are female, single, and have an educational attainment of high school level. As respondents describe domestic crime in terms of physical abuse, the highest weighted mean is "Inflicting physical harm," which resulted in an agreement. As respondents describe sexual abuse, the highest weighted mean is "Using force, coercion, guilt, or manipulation or failing to consider the victim’s desire to have sex," which resulted in agreement in verbal interpretation. In terms of respondents’ descriptions of emotional abuse, "consistently disregarding, ignoring, or neglecting the victim’s requests and needs" received the highest weighted mean with agree in verbal interpretation; in terms of verbal abuse, "threatening to hurt or kill the victim or her children, family, pets, property, or reputation" received the highest weighted mean, and in terms of the problem encountered in the method of prevention, "Lack of understanding and awareness of domestic crime methods of prevention" received the highest weighted mean as agree in verbal interpretation. The researchers recommended that Barangay officials develop a better action plan to increase public awareness and understanding of domestic violence as well as the signs of abuse. Citizens must be interested in learning about domestic violence and the signs of abuse in order to be aware of it and prevent some probleMs. Criminology students study domestic crime and are aware of domestic crime and abuse in order to have knowledge and understanding of these types of crime. Victims must be aware of the methods for preventing domestic violence in order to avoid the events they have witnessed.